2020
DOI: 10.20944/preprints202005.0254.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Process Optimisation of Low-caffeine Coffee Using Steam Treatment

Abstract: In addition to being a source of freshener, coffee has an enormous possibility to be developed as a source of antioxidants for functional beverages. However, efforts to increase the value added of coffee as a health functional drink are still hindered by the presence of high level of caffeine, which is thought to have adverse effects on health, especially for coffee lovers who are vulnerable to caffeine. This study aims to optimise the steaming duration to produce low caffeine coffee while maintaining the sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Compared with the raw material, the simultaneous extraction and decaffeination using hot water successfully reduced the caffeine content in decaffeinated green coffee bean powder-based beverages by as much as 14.35 to 30.56 %. This finding is in line with Anggriawan et al [29], who reported that the caffeine content in green coffee beans decreased by 28.20 % than the raw material after the steam pretreatment process. Moreover, this study's caffeine percentage was lower than Sinaga et al [18], who reported decreased caffeine content from 2.6 % in green bean coffee to 1.04 % in decaffeinated green bean coffee using hot water as a solvent, meaning caffeine content decreased by 60 %.…”
Section: Caffeine Contentsupporting
confidence: 91%
See 2 more Smart Citations
“…Compared with the raw material, the simultaneous extraction and decaffeination using hot water successfully reduced the caffeine content in decaffeinated green coffee bean powder-based beverages by as much as 14.35 to 30.56 %. This finding is in line with Anggriawan et al [29], who reported that the caffeine content in green coffee beans decreased by 28.20 % than the raw material after the steam pretreatment process. Moreover, this study's caffeine percentage was lower than Sinaga et al [18], who reported decreased caffeine content from 2.6 % in green bean coffee to 1.04 % in decaffeinated green bean coffee using hot water as a solvent, meaning caffeine content decreased by 60 %.…”
Section: Caffeine Contentsupporting
confidence: 91%
“…The mathematical model selection of each response (caffeine content, total phenol, and antioxidant activity (IC50)) of green coffee bean powder affected by the extraction and decaffeination process was listed in Table 4. Based on Table 4, all the observed responses were followed by the quadratic model with a significant model range of 0.0013 to 0.3135 [29]. Solano et al [30].…”
Section: Model Fittingmentioning
confidence: 99%
See 1 more Smart Citation
“…The criterion for 'aftertaste' (0.222) in this sensory coffee test shows that the panelists make it the second criterion after 'flavor', as seen on the analysis result of coffee taste criteria assessment in Table 2. 'Aftertaste' is a term used to express the taste left in the mouth and create an experience of preferred coffee taste, where there are two driving attributes that influence overall fondness to the coffee, which are bitterness and aftertaste (Anggriawan et al, 2020). It is necessary to understand that sometimes the same coffee may give a different aftertaste among coffee connoisseurs.…”
Section: Assessment Of Taste Sensorymentioning
confidence: 99%
“…The steaming process in coffee can increase consumer preference for coffee because it can increase the bitter taste and after taste in coffee caused by reduced caffeine and polyphenol content. The length of the steaming process has a significantly different effect on the taste and color of the coffee [9]. The roasting process aims to get the best color and aroma in coffee, and the longer roasting time can increase bitterness and reduce fruit acidity and sweet taste [10].…”
Section: Introductionmentioning
confidence: 99%